Modeling and Simulation of a Triple Effect Evaporator for the Concentration of Natural Juices - Avalo, Belkis; Varela, Alfredo (Rev. Téc. Fac. Ing. Univ. Zulia)
The concentration process for evaporation on each effect was modeled in a system of nine differential equations and thirteen algebraic equations which allowed solving the system using the fourth order Runge-Kutta numeric method on the level, composition and temperature variables using a simulation program designed on Visual Basic 6.0 and experimental data from of peach juice concentration process. Regarding primary conditions, in the effect one was used liquid level equivalent to 0.56m, feeding composition: 0.028° Brix and temperature on the effect one: 32°C for starting. Feeding composition variation to effect one was varied only within a rank of 2-5° Brix, with a manometric pressure for the effect one of 34.5KPa, effect two and three vacuum pressure of 46.7KPa and 60.0KPa. The simulation program reports values in the temperature variables, liquid level and concentrated fluid composition, steam flowing and concentrated fluids, with a maximum relative error of 3.55% in the temperature variable and 9.75% in the concentration variable for the effect three.